Modes of action of Interior Troops in the event of a mass confrontation of citizens in the event of inter-ethnic conflict - Orlov, М. М.; Halep, V. V.; Shapovalov, О. I. (Honor and Law, 2019)
Reasonable methods of action of internal forces in the event of a mass confrontation of citizens in the event of inter-ethnic conflict . This brief description of the system of regional government entities conflict and internal troops and block multilevel barrage of obstacles that are part of combat formations of troops.